Frequency of complementary and alternative medicine utilization in hypertensive patients attending an urban tertiary care centre in Nigeria - Okubadejo Njideka U; Amira Oluwatoyin C (BMC, 2007)
Abstract Background To study the frequency and pattern of use of complementary and alternative medicine (CAM) in patients with essential hypertension attending a tertiary hypertension clinic. Methods Two hundred and twenty-five consecutive hypertensive patients attending the hypertension clinic of the Lagos University Teaching Hospital over a 3-month period were interviewed. Socio-demographic data, duration of hypertension, clinic attendance, current blood pressure, and compliance to conventional medications was documented. CAM utilization was explored using both structured and open-ended questions. Results There were 90 (40%) male and 135 (60%) female patients with mean age ± SD overall was 55.1 ± 12.4 years. 88 (39.1%) of the respondents used CAM. Herbal products were the most commonly used CAM type. Amongst the CAM users, the most common herbal product used was garlic (69.3%). Others were native herbs (25%), ginger (23.9%), bitter leaf (Vernonia amygdalina) (9.1%), and aloe vera (4.5%). 2.5% used spiritual therapy. There was no difference in the clinical characteristics, socio-economic status, and blood pressure control of CAM users and non-users. Patients who utilized CAM had higher BMI compared with those who did not, but the difference was not statistically significant (mean BMI ± SD of 29.1 ± 5.6 vs 27.1 ± 5.9 kg/m2; P = 0.05). Conclusion A significant proportion of hypertensive patients attending our tertiary facility and receiving conventional treatment also use CAM therapies. Clinicians need to be aware of this practice, understand the rationale for this health-seeking behaviour, proactively enquire about their use, and counsel patients regarding the potential of some of the therapies for adverse reactions and drug interactions.